Impact of characteristics of the board of directors on the truthfulness of financial statement information of listed firms in Vietnam - Hong Thi Xuan Nguyen; Huyen Thu Pham; Nhung Thi Dao; Nga Thi Nguyen (Cogent Business & Management, 2022)
Truthfulness in accounting creates a significant concern for academics, practitioners, regulators, and the press. This study investigates the influence of the Board of Directors (BOD) characteristics on the truthfulness of accounting reports. The research uses quantitative methods to test hypotheses with a sample of 747 listed companies from 2008 to 2020. The results illustrate that the frequency of meetings of the Board of Directors, Board expertise, and Board independence positively influence the truthfulness of the financial reporting. At the same time, the duality of the BOD negatively affects the truthfulness of the financial reporting. Based on the findings, the study recommends developing an appropriate corporate governance system to increase the truthfulness of financial reporting for listed firms in Vietnam.
Keywords: G32; G30; M41; 650; Vietnam; listed companies; board of directors; the truthfulness of financial reports